Engaging the private sector to improve antimicrobial use in the community: experience from accredited drug dispensing outlets in Tanzania - Valimba, Richard (BioMed Central, 2014)
OBJECTIVES: A public-private partnership in Tanzania launched the accredited drug dispensing outlet (ADDO) program to improve access to quality medicines and pharmaceutical services in rural areas. ADDO dispensers play a potentially important role in promoting the rational use of antimicrobials, which helps control antimicrobial resistance (AMR). The study objectives were to 1) improve dispensing practices of antimicrobials, 2) build ADDO dispensers’ awareness of the consequences of misusing antimicrobials, and 3) educate consumers on the correct use of antimicrobials through the use of printed materials and counseling. METHODS: Our intervention targeted ADDO dispensers and community members in Kilosa district. We promoted AMR awareness using posters hung in public places, health facilities, and ADDOs; sensitizing 84 health care providers on AMR issues; and providing training and on-site support for 124 ADDO dispensers to increase their AMR knowledge and dispensing skills. Baseline and endline assessments included direct observation of dispensers’ practices; interviews with ADDO dispensers (71 at baseline and 68 at endline) regarding dispensing experiences; 230 exit interviews with ADDO customers regarding use of antimicrobials during monitoring visits; and review of ADDO records. Indicators were based on product availability, dispensing practices, customers’ knowledge of how to take their medicines, and dispenser and public awareness of the AMR threat. RESULTS: Availability of tracer antimicrobials increased by 26% (p = 0.0088), and the proportion of ADDOs with unauthorized items decreased from 53% to 13% (p = 0.0001). The percentage of ADDO dispensers following good dispensing practices increased from an average of 67% in the first monitoring visit to an average of 91% during the last visit (p = 0.0001). After the intervention, more dispensers could name more factors contributing to AMR and negative consequences of inappropriate antimicrobial use, and over 95% of ADDO customers knew important information about the medicines they were dispensed. CONCLUSIONS: Providing educational materials and equipping ADDO dispensers with knowledge and tools helps significantly improve community medicine use and possibly reduces AMR. The number of community members who learned about AMR from ADDO dispensers indicates that they are an important source of information on medicine use.